PENGARUH KONDISI KULTUR YANG BERBEDA TERHADAP AKTIVITAS ANTIOKSIDAN METABOLIT SEKUNDER KAPANG ENDOFIT ASAL AKAR KUNYIT - Eris Septiana; Partomuan Simanjuntak (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Antioxidant is an interesting topic due to their capability to inhibit free radical and prevent damage because of oxidative processes. Endophyt fungi is one of antioxidant compound resources in nature. The low yield to gain antioxidant compound from fungi challenges to look for the composition of media and optimalization of growth conditions. This research aimed to know the effect of medium condition in different carbon and nitrogen sources as well as initial pH towards antioxidant activity of endophyt fungi Bo.Ci.Cl.A3. Shaker fermentation was used on 120 rpm at room temperature for 14 days. The carbon sources were glucose, sucrose, and starch and nitrogen sources were NaNO3, NH4NO3, and yeast extract with initial pH at 5, 7, and 9. Ethyl acetate was used as extractor. The results showed that endophyt fungi can produce secondary metabolite as antioxidant at all variation of fermented media. The nitrogen source of yeast extract could increase antioxidant activity of endophyt fungi Bo.Ci.Cl.A3, while other sources such as nitrogen source, carbon sources, and different initial pH on the basal medium that were used did not give increasing antioxidant activity. The conclusion of this research was the substitution of nitrogen source with yeast extract (3 g/L) on the basal medium Czapek Dox’s Broth could increase antioxidant activity of endophyt fungi Bo.Ci.Cl.A3.